2016
DOI: 10.1590/1807-3107bor-2016.vol30.0049
|View full text |Cite
|
Sign up to set email alerts
|

Location and classification of Canalis sinuosus for cone beam computed tomography: avoiding misdiagnosis

Abstract: The aim of this study was to assess the presence, location and, multiplanar distance of the canalis sinuosus (CS) between the incisive foramen and the anterior maxillary alveolar ridge using cone beam computed tomography (CBCT). Therefore, 500 CBCT maxillary images obtained from male and female patients aged 20 to 80 years were selected to assist in the dental treatment. Low-quality tomographic images were discarded. All images were captured with the i-CAT TM Classic tomograph and assessed using the XoranCat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
3
22
2
5
Order By: Relevance
“…They found the frequency of 52.1%. Evaluation of 500 CBCT scans by Manhaes Junior et al [9] is another largest sample size. According to their report, frequency of CS was 36.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found the frequency of 52.1%. Evaluation of 500 CBCT scans by Manhaes Junior et al [9] is another largest sample size. According to their report, frequency of CS was 36.2%.…”
Section: Discussionmentioning
confidence: 99%
“…von Arx et al [16] reported that the most commonly found region was palatal to central incisors. Manhaes Junior et al [9] reported that it was "beside the incisive foramen" and de Oliveira Santos et al [2] found it "near the incisors or canine". Machado et al [8] defined the most commonly seen location as "palatal to the anterior maxillary teeth".…”
Section: Discussionmentioning
confidence: 99%
“…Manhães Júnior ve ark., 500 bireyin KIBT görüntülerinde; voksel boyutu 0,25 mm 3 ve 0,25 mm aksiyal kalınlıktaki kesitlerle gerçekleştirilen çalışmalarında CS'nin alveolar seviyedeki açıklıklarının nazal kavite tabanı, bukkal kortikal kemik ve alveolar kret tepesine olan mesafesini incelemişlerdir. 17 Bu çalışmanın sonucu olarak, %36,20 oranında alveolar seviyede CS saptamışlardır. Ça-lışmamızda da alveolar seviyede sonlanan 1 mm'den geniş çapı olan CS sıklığı ortalama %4,37 bulunmuş olup, bu sonuç Manhães Júnior ve ark.nın CS oranından düşüktür.…”
Section: Discussionunclassified
“…Ça-lışmamızda da alveolar seviyede sonlanan 1 mm'den geniş çapı olan CS sıklığı ortalama %4,37 bulunmuş olup, bu sonuç Manhães Júnior ve ark.nın CS oranından düşüktür. 17 Ancak, onların çalışmasında dâhil edilen CS çapları ile ilgili bir bilgi verilmemiştir. Dolayısıyla iki çalışma arasındaki bu farkın 1 mm'den küçük çaptaki CS'lerden kaynaklanabileceği düşünülmektedir.…”
Section: Discussionunclassified
“…In the past, these morphological changes were hardly detected as a result of poor quality images which could lead to intraoperative complications in which the etiology was unknown during a surgical procedure in the anterior maxillary region [4]. The technical developments in diagnostic imaging have increased the accuracy of the diagnostic data obtained, particularly the use of CBCT [5,6].…”
Section: Introductionmentioning
confidence: 99%